Immortalizing Cells for Human Consumption - Emily Soice (MDPI AG, 2021)
The need to produce immortal, food-relevant cell lines is one of the most pressing challenges of cellular agriculture, the field which seeks to produce meat and other animal products via tissue engineering and synthetic biology. Immortal cell lines have a long and complicated story, from the first recognized immortal human cell lines taken from Henrietta Lacks, to today, where they are used to assay toxicity and produce therapeutics, to the future, where they could be used to create meat without harming an animal. Although work in immortal cell lines began more than 50 years ago, there are few existing cell lines made of species and cell types appropriate for cultured meat. Cells in cultured meat will be eaten by consumers; therefore, cultured meat cell lines will also require unique attributes not selected for in other cell line applications. Specifically, cultured meat cell lines will need to be approved as safe for consumption as food, proliferate and differentiate efficiently at industrial scales, and have desirable taste, texture, and nutrition characteristics for consumers. This paper defines what cell lines are needed, the existing methods to produce new cell lines and their limitations, and the unique considerations of cell lines used in cultured meat.